2019
DOI: 10.1002/nau.24029
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal voiding frequency does not describe nocturia‐related bother

Abstract: Aim Nocturia frequency has been used as a measure of treatment efficacy for nocturia even though fluctuation of the symptom over time has been well described in the literature. Additionally, given the multifactorial causal pathway and clinically relevant comorbidities, frequency alone may be an insufficient marker of treatment direction. The aim of this study was to investigate factors associated with nocturia‐related bother to identify additional variables that may capture the impact of nocturia, direct clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This finding is of utmost importance as this bother not only reflects the problem of getting up during the night, but also refers to the general quality of life and well-being of the patient. 30,31 Previously, it has been found that nighttime LUTS were more bothersome than daytime LUTS, 32 which can be explained by compromised sleep. 32,33 The decrease in nocturnal frequency and the improvement of bother can mostly likely be explained by the positive impact of HT on sleep, as the SLEEP sum score decreased significantly after treatment with both E þ P and TSEC.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is of utmost importance as this bother not only reflects the problem of getting up during the night, but also refers to the general quality of life and well-being of the patient. 30,31 Previously, it has been found that nighttime LUTS were more bothersome than daytime LUTS, 32 which can be explained by compromised sleep. 32,33 The decrease in nocturnal frequency and the improvement of bother can mostly likely be explained by the positive impact of HT on sleep, as the SLEEP sum score decreased significantly after treatment with both E þ P and TSEC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the International Continence Society defines nocturia as one or more voids during the main sleep period, for this study the clinically relevant definition of at least two voids per night was applied and referred to throughout the text as ‘disruptive nocturia’ 10 . Nocturia frequency was collected in two ways: as an open‐ended question (self‐report) and by derivation of the number of episodes on a bladder diary (actual nightly voids).…”
Section: Methodsmentioning
confidence: 99%
“…More voids per night are also significantly associated with greater impact on both physical and mental health components of quality of life scores 2 . The following aspects of sleep have been reported significantly more often by individuals who void twice or more each night compared with those who do not: restless sleep, first undisturbed sleep time (FUST) less than 3 hours, difficulty falling back to sleep after voiding, insufficient overall sleep, low energy or fatigue during the day and worry that nocturia will get worse 3,4 . This severity of nocturia of at least twice at night has also been demonstrated to be significantly associated with more adverse health outcomes than less frequent night voiding.…”
Section: Disclosure Of Interestsmentioning
confidence: 99%